2015
DOI: 10.1080/10502556.2015.1025900
|View full text |Cite
|
Sign up to set email alerts
|

Parents Forever: Evaluation of an Online Divorce Education Program

Abstract: Divorce education programs are conducting increasingly rigorous impact evaluations to assess if their curriculum improves parenting practices, reduces conflict in the coparenting relationship, and improves outcomes for children. This article presents a 6-month follow-up evaluation of the online version of Parents Forever, an 8-hour divorce education course developed by the University of Minnesota Extension. At follow-up, parents ( N = 232) reported significant improvements on several questions about postdivorc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…An unanswered question in the literature is whether shorter, more broadly implemented programs have more or less impact than longer programs that are differentially mandated. Moreover, although some professionals advocate for longer programs that offer more depth and breadth (Becher et al, 2015), resulting in longer duration (e.g., 4 hours or more), others suggest brevity may still be effective (e.g., Brotherson et al, 2010).…”
Section: Common Practices In Divorce Educationmentioning
confidence: 99%
“…An unanswered question in the literature is whether shorter, more broadly implemented programs have more or less impact than longer programs that are differentially mandated. Moreover, although some professionals advocate for longer programs that offer more depth and breadth (Becher et al, 2015), resulting in longer duration (e.g., 4 hours or more), others suggest brevity may still be effective (e.g., Brotherson et al, 2010).…”
Section: Common Practices In Divorce Educationmentioning
confidence: 99%
“…Some research has found minimal evidence of effectiveness among these programs with regard to enhancing the coparenting relationship (Goodman et al, ), but others have found them moderately effective ( Fackrell, Hawkins, & Kay, ). In our previous evaluations of an 8‐hour divorce education program, Parents Forever, we have found mixed evidence for the programs' impact on the coparenting relationship (Becher et al, , ). Because of the importance of the coparenting alliance for families experiencing divorce and the mixed results of current education efforts, more research is needed to better decipher which variables and interactions influence the coparenting alliance and, in turn, inform prevention programs for divorcing families.…”
mentioning
confidence: 94%
“…However, the effects of behavior change techniques may be more relevant to target ACE outcomes than engagement outcomes, given that they are specifically designed to promote change in target parenting behavior. Inspection of the studies included in this analysis (n=3) found that all programs with behavior change techniques were more likely to improve target ACE outcomes compared with programs without behavior change techniques [47,122,147].…”
Section: Delivery Strategiesmentioning
confidence: 99%